The Effect of Advertising and Product Quality on Consumer Purchase Interest On Scoop & Skoops Products (Case Study of Scoop & Skoops Consumers in Bandung City) - Andhi Sukma; Donny Rizky Ramdhani (Universitas Batanghari, 2023)
Scoop & Skoops was established to be the first Ice Cream Shop in Indonesia that carries the Industrial CafÃ© concept. The efforts made by the company in advertising and different product quality are aimed at increasing consumer buying interest. Basically consumer buying is interested in determining or choosing a product. A person's desire to buy something requires a stimulus and stimulation that arises from both external and internal. The type of research used in this research is descriptive research. This research model uses a quantitative approach that is descriptive in nature and tested by IBM SPSS Statistics 26. The results of this study are that simultaneously advertising and product quality have an effect on purchase interest. Partially, advertising and product quality have a positive effect on purchase interest.